Exploring the Potential of Multiple Intelligences as an Effort to Improve Adolescent Health Holistically - Meita Dhamayanti; Veranita Pandia; Nita Arisanti; Hesty Widyasih; Devi Azriani; Lusiana El Sinta Bustami; Made Yos Kresnayana (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
The community services aim to identify multiple intelligences to optimize adolescent health holistically. Methods of implementation with surveys and education. The survey was conducted with multiple intelligence cards filled out by adolescents to obtain multiple intelligence data. Adolescents circled the answers according to the statements on the multiple intelligence cards that fit their circumstances. Score 1 if very inappropriate, score 2 if not very appropriate, score 3 if appropriate, and score 4 if very appropriate to the adolescent. Analysis using descriptive methods. This community service activity was carried out from April to June 2023. The location of the activity was a private junior high school in Ciparay District, Bandung Regency, West Java. The target of the activity was junior high school teenagers. The number of participants was 149 teenagers. The community services results show that the first and second highest rank is interpersonal intelligence. The third rank is kinesthetic intelligence. The conclusion is that most students have interpersonal intelligence. The school should map students according to their needs so it can optimize their potential to increase adolescent health holistically.